"But if Locals Are Poorer than You, How Would You Justify Additional Help?": Rethinking the Purpose of Sensitive Interview Questions. (17th July 2018) - Cole, Georgia
Abstract: Drawing upon interviews with Eritrean refugees in Uganda in late 2016, this article documents their responses to the question of how to justify support to refugees in contexts where similar assistance is not provided to nationals. It thus aims to add the perspective of displaced persons to a debate largely populated by the words of host communities, governments and humanitarian organisations, and various pro-immigration lobby groups. Given the sensitivity of this question, however, this article also provides an extensive justification as to why this angle of enquiry was pursued. To do so, it argues that asking potentially "difficult" questions during certain interviews can help pluralise how we represent "refugees' voices", convey the multi-facetedness of an individual's identity and agency, including that of the researcher, and signal a move away from methodologies that inadvertently victimise.